Dejavniki izvajanja mehke zakonodaje EU na področju enakosti spolov - Topolinjak, Simona (Družboslovne razprave, 2013)
This paper examines various implementation factors of the European Union's soft policy in the field of gender equality in Slovenia. We focus on implementation of the principle of the balanced representation of women and men in decision-making processes in the fields of politics, science and the economy, where the proportion of women in top positions remains low. Based on an analysis of EU and Slovenian legislation and interviews with relevant governmental and non-governmental actors at the EU and national levels, it was found that because of the adopted soft law in this area it is the national government, which can select public policy instruments and adapt them to its own aspirations, that is the most important player when it comes to implementation. Pressure from the EU was stronger in the accession negotiations when Slovenia was joining the EU and also when interest groups work together.
Keywords: Enakost moških in žensk; Equality between men and women; Decision-making; Odločanje; Javna politika [V4.3]; Public policy [V4.3]; Politika Skupnosti; Slovenija; Community policy; enakost spolov; gender equality; procesi odločanja; Slovenia; European Union; Evropska unija; javna politika; politika EU; izvajanje javnih politik; mehka zakonodaja